Genetic variants in IL15 promoter affect transcription activity and intramuscular fat deposition in longissimus dorsi muscle of pigs. (22nd November 2017) - He, D.; Jiang, Z.; Tian, Y.; Han, H.; Xia, M.; Wei, W.; Zhang, L.; Chen, J.
Summary: Intramuscular fat (IMF) content is a key aspect of pork quality. Elucidation of intramuscular adipocyte regulation mechanisms is important for improving IMF content. Intramuscular adipocytes are dispersed among muscle fibers, so they are inclined to be affected by muscle‐derived factors. Interleukin‐15 is a major muscle‐secreted factor. In this study, the genetic and physiological impacts of IL15 on adipogenesis is investigated. The promoter region of IL15 was scanned by comparative sequencing using two DNA pools of high‐ and low‐IMF individuals. Two SNPs, c.–342C>T (ss2137497757) and c.–334G>A (ss2137497756) (the translation start site is designated as +1), were identified with reverse allele distribution in these two groups. Genotyping by allele‐specific PCR revealed that the two SNPs were completely linked. The IMF content of TA/TA individuals was lower than that for CG/CG ones, whereas the IL15 expression level was higher in T‐A/T‐A individuals. Luciferase assaying also revealed that the T‐A haplotype promoter had higher transcription activity. Meanwhile, the effect of interleukin‐15 on adipocyte differentiation was further assessed in vitro . Results showed that interleukin‐15 suppressed preadipocyte proliferation in a dose‐dependent manner. The cell cycle of preadipocytes was arrested, and apoptosis was induced. Oil Red O staining and triglyceride quantification indicated that adipocyte differentiation was also inhibited by interleukin‐15. The mRNA levels of PPARG and FABP4 decreased markably upon interleukin‐15 treatment. Taken together, we identified two completely linked SNPs in the porcine IL15 promoter region that could alter IL15 transcription activity. As interleukin‐15 can inhibit porcine adipocyte differentiation, these promoter mutations could affect IMF deposition by producing differential levels of muscle‐derived interleukin‐15.